Oral Postdialysis Cholecalciferol Supplementation in Patients on Maintenance Hemodialysis: A Dose-Response Approach - Eric Descombes; Benoit Fellay; Ould Maouloud Hemett; Jean-Luc Magnin; Gilbert Fellay (International Journal of Nephrology)
The aim of the present study was to evaluate the dose of postdialysis cholecalciferol needed to maintain the 25-hydroxyvitamin D [25(OH)D] levels in the optimal range of 75–150 nmol/L. Twenty-six patients who had low baseline 25(OH)D levels (mean 27.5±14.9 nmol/L) were studied. The 25(OH)D levels were measured every 2 months for one year. During the first two months, all the patients received 2000 IU of cholecalciferol after each hemodialysis (=6000 IU/wk). Thereafter, the dose was individualized and adapted every 2 months by administering 1 to 6 cholecalciferol tablets (2000 IU each) per week (total weekly dose = 2000–12000 IU/wk). During cholecalciferol supplementation, the 25(OH)D concentrations rapidly increased from baseline to 140.1±28.3 nmol/L at month 6 and 95.6±20.9 nmol/L at month 12. At month twelve, 86% of the patients had 25(OH)D levels within the target range with a mean dose of 5917±4106 IU/wk of cholecalciferol; however, the amount needed to maintain these levels varied widely from 0 (n=2) to 12000 IU/wk (n=5). In conclusion, postdialysis cholecalciferol prescription is quite effective in correcting vitamin D deficiency/insufficiency, but the amount of cholecalciferol needed to maintain the 25(OH)D levels within the optimal range over the long-term varies widely among patients and must be individualized.